-3(-3b+5a)=

Simple and best practice solution for -3(-3b+5a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-3b+5a)= equation:


Simplifying
-3(-3b + 5a) = 0

Reorder the terms:
-3(5a + -3b) = 0
(5a * -3 + -3b * -3) = 0
(-15a + 9b) = 0

Solving
-15a + 9b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9b' to each side of the equation.
-15a + 9b + -9b = 0 + -9b

Combine like terms: 9b + -9b = 0
-15a + 0 = 0 + -9b
-15a = 0 + -9b
Remove the zero:
-15a = -9b

Divide each side by '-15'.
a = 0.6b

Simplifying
a = 0.6b

See similar equations:

| 3(8+7n)=150 | | (1/3)-(1/A)/(3-A)/3 | | 3(x-2)+7(9x-3)=5(9x-7)-12(x-3) | | (1/3)-(1/2)/(3-A)/3 | | 2x^2+tx+10=0 | | 7(-4)-5(-7)-7=0 | | 1/3-1/A/3-A/3 | | -16t^2+105t+200=0 | | 12x=x+2 | | 8=8v-4+8v | | .30x+.25y=13.30 | | p^2-8p+5=5 | | 72.9=9m | | 1.55=0.93 | | -71=-7x-2(3x-10) | | 4s-8=2s+16 | | -5=300 | | (5x-11)+(3x+1)=78 | | [4(30-5)]/-10/2 | | -4-(-16-7)=20-(-4+21) | | 120-v=232 | | y=-4.9x^2+12x+1.8 | | 1/2x-1/4y2 | | (5/3)-(2/(2m | | Ln(t^2-6t+9)=0 | | 20-2x=1.5x | | 4(y-3)=3(y-6) | | log1/3(27) | | Y=12sinx+9cosx | | 5st+r-3xy=xy+2xt | | 4z-0.8=5z | | 12-.2*x=4 |

Equations solver categories